Electrolyte membrane for all-solid-state battery, all-solid-state battery and preparation method of all-solid-state battery
By introducing the oxide layer of the sulfide electrolyte into the electrolyte membrane of the all-solid-state battery, the problem of the electrochemical oxidation reaction between the sulfide electrolyte and the composite cathode layer is solved, extending the cycle capacity of the battery, and reducing the weight and energy of the battery. density.
Patent Information
- Application Number
- CN202411609173.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-01-21
AI Technical Summary
In an all-solid state battery, at the contact interface between the sulfide electrolyte layer and the composite positive electrode layer, metal ions and the sulfide electrolyte layer undergo an electrochemical oxidation reaction, resulting in a significant increase in the internal resistance of the battery and failure. The prior art is separated by adding a halide electrolyte cushion layer, but the thickness of the cushion layer is relatively large, affecting the battery weight and energy density.
A electrolyte film, including the first electrolyte layer and the second electrolyte layer, the first electrolyte layer is composed of sulfide electrolyte, and the second electrolyte layer is composed of oxide of the vulcanic electrolyte. The electrolyte layer, the second electrolyte layer has a small thickness, which can effectively isolate the first electrolyte layer and the positive pole layer.
Through the existence of the second electrolyte layer, the electrochemical oxidation response between the electrolyte and the positive layer of the sulfide and the positive pole layer is avoided, and the long cycle capacity of the battery is prolonged. Due to the small thickness of the second electrolyte layer, the battery weight and energy density will not be increased, and the energy density will be reduced. The production process and cost of electrolyte film.
Smart Images

Figure CN119340462A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of all-solid-state batteries, and in particular to an electrolyte membrane for an all-solid-state battery, an all-solid-state battery and a preparation method thereof. Background Art
[0002] Lithium-ion batteries use lithium ions as carriers. Lithium ions undergo reversible electrochemical reactions between the positive and negative electrodes of the battery to achieve energy storage and release. Lithium-ion batteries have the advantages of high energy density (e.g. 100-300Wh / kg), no memory effect, ultra-low self-discharge rate, and low cost, making them the mainstream energy storage and supply system for 3C digital and automotive power batteries. All-solid-state batteries are a form of lithium-ion batteries that use solid electrolyte materials that are non-flowable at a certain temperature (e.g. below 150°C) to replace flowable electrolytes to assist in the transmission of lithium ions, thereby improving the safety of lithium-ion batteries.
[0003] During the charging and discharging process of lithium-ion batteries, Li + Insertion and deinsertion back and forth between the two electrodes: During charging, Li + It is deintercalated from the positive electrode and embedded into the negative electrode through the electrolyte, and the negative electrode is in a lithium-rich state; the opposite is true during discharge. Lithium-ion batteries can be divided into three categories based on the battery form: liquid, semi-solid, and all-solid. Liquid batteries use flowable electrolytes as electrolytes, semi-solid batteries reduce the amount of electrolytes used or use polymer electrolytes instead, and all-solid batteries are built with non-flowing solid electrolytes.
[0004] All-solid-state batteries based on sulfide electrolytes can achieve a higher energy density. For example, a 20Ah battery cell based on a high-nickel ternary and graphite chemical system can achieve an energy density of 250Wh / kg, and a 20Ah battery cell based on a special negative electrode chemical system such as high nickel and silicon, lithium, and silver carbon can achieve an energy density of 350-400Wh / kg. The research on all-solid-state batteries based on sulfide electrolytes has been relatively short. Compared with sulfides, halides are more stable and will not undergo combustion reactions. In addition, sulfides produce highly toxic H2S gas when in contact with water, while the reaction products of halides when in contact with water are non-toxic. Therefore, the introduction of halides into all-solid-state batteries has become one of the technical development trends in this field.
[0005] The typical components of solid halide electrolytes are Li a MX y , wherein the metal element M is generally a metal in a positive trivalent state to a positive pentavalent state, and X is a halogen element, such as Cl. 3-5+It has a certain oxidizing property, and the oxidation potential of Cl element is high, so the halide electrolyte is in stable contact with the highly oxidizing delithiated layered oxide positive electrode. Usually, the halide electrolyte, oxide positive electrode material, conductive carbon and binder are compounded in a certain proportion to form a composite positive electrode, and the composite positive electrode layer is stacked with the sulfide electrolyte layer and the negative electrode layer to construct a halide all-solid-state battery. The composite positive electrode layer has both ion and electron conduction capabilities. However, at the contact interface between the composite positive electrode layer and the sulfide electrolyte layer, the M with a certain oxidizing property in the composite positive electrode layer 3-5+ can react with S in the sulfide electrolyte layer 2- Electrochemical oxidation reaction occurs to form M x S y Low ion conductivity and electron conductivity compounds such as fluorine lead to a significant increase in the internal resistance of the battery and battery failure.
[0006] To address this problem, the prior art adds a halide electrolyte cushion layer between the sulfide electrolyte layer and the composite positive electrode layer to separate the M 3-5+ With S 2- , avoiding the chemical reaction between the two and maintaining the normal operation of the battery. However, sulfide electrolytes are relatively stable to weak polar solvents and binders, and can be slurried normally to cast ultra-thin electrolyte layers; halide electrolytes are unstable to most solvents and binders, making it difficult to slurry and extremely difficult to make thin layer electrolytes. The thickness of the halide electrolyte cushion layer is relatively thick, generally exceeding 5μm; in addition, after the halide electrolyte interacts with the solvent and binder, the lithium ion conductivity drops to less than 20% of the original. Therefore, the halide electrolyte cushion layer significantly increases the impedance, which is not conducive to the battery rate performance. In addition, the density of the halide electrolyte is greater than that of the sulfide, and the added thick cushion layer significantly increases the weight of the battery, which is not conducive to the battery energy density. Summary of the invention
[0007] In view of the above problems in the prior art, the present disclosure provides an electrolyte membrane for an all-solid-state battery, an all-solid-state battery and a method for preparing the same.
[0008] In a first aspect, the present disclosure provides an electrolyte membrane for an all-solid-state battery, comprising a first electrolyte layer, the first electrolyte layer comprising at least one sulfide electrolyte, the first electrolyte layer comprising a positive electrode connection side and a negative electrode connection side arranged opposite to each other, the positive electrode connection side being used to connect to the positive electrode of the solid-state battery, the negative electrode connection side being used to connect to the negative electrode of the solid-state battery, the positive electrode connection side of the first electrolyte layer being provided with a second electrolyte layer, the second electrolyte layer comprising an oxide of the sulfide electrolyte.
[0009] Optionally, the thickness of the second electrolyte layer is 10-2000 nm.
[0010] Optionally, the oxide of the sulfide electrolyte is obtained by oxidizing the sulfide electrolyte.
[0011] Optionally, the sulfide electrolyte is at least one of LPSC, LPSBr, LSPS and LPSI.
[0012] Optionally, the thickness of the first electrolyte layer is 15-100 μm; the thickness of the second electrolyte layer is 20-1000 nm.
[0013] Optionally, the second electrolyte layer includes an extension layer close to the positive electrode connection side, the thickness of the extension layer is 8-100 nm, and in the extension layer, the molar ratio of sulfur atoms to oxygen atoms is 1:(0.1-5).
[0014] In a second aspect, the present disclosure provides an all-solid-state battery, comprising a positive electrode layer, a negative electrode layer and an electrolyte membrane located between the positive electrode layer and the negative electrode layer, wherein the electrolyte membrane is the electrolyte membrane as described in the above technical solution, the electrolyte membrane is connected to the negative electrode layer through the first electrolyte layer, and the electrolyte membrane is connected to the positive electrode layer through the second electrolyte layer.
[0015] In a third aspect, the present disclosure provides a method for preparing an all-solid-state battery, wherein the all-solid-state battery may be the all-solid-state battery as described in the above technical solution, comprising:
[0016] Performing oxidation treatment on one side of an electrolyte matrix to obtain an electrolyte membrane, wherein the electrolyte matrix includes at least one sulfide electrolyte, the oxidation treatment temperature is 70-250° C., the oxidation treatment time is 0.3-12 hours, and the electrolyte membrane includes a first electrolyte layer and a second electrolyte layer formed by a portion of the electrolyte matrix after the oxidation treatment;
[0017] The electrolyte membrane is connected to the positive electrode layer and the negative electrode layer respectively to obtain an all-solid-state battery including the electrolyte membrane, the positive electrode layer and the negative electrode layer, wherein the first electrolyte layer is connected to the negative electrode layer, and the second electrolyte layer is connected to the positive electrode layer.
[0018] Optionally, the oxidation treatment includes: placing one side of the electrolyte matrix in a compressed air atmosphere or an oxygen atmosphere, and treating at 80-200° C. for 0.5-10 h.
[0019] In a fourth aspect, the present disclosure provides a method for preparing an all-solid-state battery, wherein the all-solid-state battery may be the all-solid-state battery as described in the above technical solution, comprising:
[0020] Connecting an electrolyte matrix to the negative electrode layer or forming the electrolyte matrix on one side of the negative electrode layer to obtain a first composite, wherein the electrolyte matrix includes at least one sulfide electrolyte;
[0021] The electrolyte matrix is subjected to oxidation treatment on a side away from the negative electrode layer to obtain a second composite body including an electrolyte membrane, wherein the electrolyte membrane is obtained by oxidation treatment of the electrolyte matrix, the oxidation treatment temperature is 70-250° C., and the oxidation treatment time is 0.3-12 h;
[0022] The second composite is connected to the positive electrode layer through the electrolyte membrane to obtain an all-solid-state battery including the electrolyte membrane, the positive electrode layer and the negative electrode layer.
[0023] Optionally, the oxidation treatment includes: placing the first composite body in a compressed air atmosphere or an oxygen atmosphere, and treating it at 80-200° C. for 0.5-10 h.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The present disclosure provides an electrolyte membrane for an all-solid-state battery and an all-solid-state battery, wherein the electrolyte membrane comprises a first electrolyte layer, wherein the first electrolyte layer comprises at least one sulfide electrolyte, and a second electrolyte layer is provided on the positive electrode connection side of the first electrolyte layer, wherein the second electrolyte layer comprises an oxide of the sulfide electrolyte, wherein the second electrolyte layer has good oxidation resistance relative to the first electrolyte layer, has chemical stability with respect to the positive electrode layer, and does not undergo electrochemical redox reaction with the positive electrode layer, thereby extending the long cycle capacity of the battery;
[0026] The second electrolyte layer has a relatively small thickness, which substantially does not increase the battery weight and battery energy density, and the second electrolyte layer can effectively isolate the first electrolyte layer and the positive electrode layer under the relatively small thickness;
[0027] By oxidizing the electrolyte matrix, a second electrolyte layer can be generated by an in-situ reaction on the electrolyte matrix. The second electrolyte layer has a smaller thickness and can avoid increasing the weight of the battery. The second electrolyte layer is obtained by oxidizing the electrolyte matrix and does not need to be obtained through a separate forming process such as coating, which can reduce the production process and production cost of the electrolyte membrane. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solution of the present invention, the following briefly introduces the drawings required for use in the embodiments or prior art descriptions. Obviously, the drawings described below are only some embodiments of the present invention, and for those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work.
[0029] Figure 1 The cross-sectional morphology of the electrolyte membrane obtained by pure oxygen oxidation and the distribution of O, Cl, and S elements. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solutions and advantages of the present disclosure clearer, the technical solutions in the embodiments of the present disclosure will be clearly and completely described below. It should be understood that the following embodiments are only used to explain the present disclosure and are not used to limit the present disclosure.
[0031] The present disclosure provides an electrolyte membrane for an all-solid-state battery, an all-solid-state battery and a method for preparing the same. The technical scheme in the embodiments of the present disclosure will be described clearly and completely below in conjunction with the drawings in the embodiments of the present disclosure. Obviously, the described embodiments are only part of the embodiments of the present disclosure, not all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present disclosure.
[0032] In a first aspect, the present disclosure provides an electrolyte membrane for an all-solid-state battery.
[0033] Optionally, the all-solid-state battery includes a positive electrode layer, a negative electrode layer and an electrolyte layer located between the positive electrode layer and the negative electrode layer.
[0034] The positive electrode layer of the all-solid-state battery includes a solid halide electrolyte, specifically including 10-40wt%, preferably 15-30wt% of a solid halide electrolyte. The solid halide electrolyte includes lithium ions and at least one metal ion in a positive trivalent state to a positive pentavalent state. Optionally, the solid halide electrolyte includes Li a MX y , where a and b are positive numbers, and the metal element M is a metal ion M in a positive trivalent to positive pentavalent state 3-5+ , metal ion M 3-5+ For example, Ni 4+ 、In 3+ , Nb 5+ 、Zr 4+ , X is, for example, Cl - or Br - Exemplarily, the solid halide electrolyte includes at least one of Li3InCl6, LiNbOCl4, and Li2O-ZrCl4.
[0035] The positive electrode layer also includes a positive electrode active material, specifically including 60-90 wt %, preferably 70-85 wt % of the positive electrode active material.
[0036] The electrolyte layer of the all-solid-state battery includes at least one sulfide electrolyte, and the electrolyte membrane is used as the electrolyte layer of the all-solid-state battery. The negative electrode layer of the all-solid-state battery includes at least one of graphite, silicon, silicon oxide, silicon alloy, silicon-carbon-based material composite, carbon-based material, metal oxide, tin, tin alloy and tin-carbon composite, and exemplary, the negative electrode layer of the all-solid-state battery is a silicon negative electrode layer.
[0037] Optionally, the all-solid-state battery further includes a positive electrode current collector and a negative electrode current collector, the positive electrode current collector is connected to the positive electrode layer, and the negative electrode current collector is connected to the negative electrode layer.
[0038] The electrolyte membrane includes a first electrolyte layer, which includes a positive electrode connection side and a negative electrode connection side arranged opposite to each other, the positive electrode connection side is used to connect to the positive electrode or positive electrode layer of the solid-state battery, and the negative electrode connection side is used to connect to the negative electrode or negative electrode layer of the solid-state battery.
[0039] The first electrolyte layer includes at least one sulfide electrolyte. Optionally, the sulfide electrolyte is at least one of LPSC (Li6PS5Cl), LPSBr, LSPS and LPSI.
[0040] A second electrolyte layer is provided on the positive electrode connection side of the first electrolyte layer, and the second electrolyte layer includes an oxide of the sulfide electrolyte. In the all-solid-state battery, the second electrolyte layer is located between the first electrolyte layer and the positive electrode layer of the all-solid-state battery, and compared with the sulfide lattice [PS4] unit present in the first electrolyte layer, at least part of the lattice [PS4] unit of the sulfide in the second electrolyte layer is oxidized to [PS 4-x O x ], x is a positive integer less than 4, thereby, the second electrolyte layer has higher oxidation resistance than the first electrolyte layer, has chemical stability with respect to the positive electrode layer, and does not undergo electrochemical redox reaction with the positive electrode layer, thereby extending the long cycle capacity of the battery.
[0041] Optionally, the first electrolyte layer has a thickness L1, and the second electrolyte layer has a thickness L2, L2=aL1, and the value of a is 0.0001-0.12, preferably 0.0005-0.1, for example, 0.0008, 0.001, 0.002, 0.004, 0.008, 0.01, 0.04 or 0.06. Compared with the first electrolyte layer, the second electrolyte layer has a smaller thickness dimension, which will not significantly increase the battery weight and battery energy density, and the second electrolyte layer can effectively isolate the first electrolyte layer and the positive electrode layer at a smaller thickness dimension.
[0042] Optionally, the thickness of the first electrolyte layer is 15-100 μm, for example, 20 μm, 25 μm, 30 μm, 50 μm or 75 μm.
[0043] Optionally, the thickness of the second electrolyte layer is 10-2000 nm, preferably 20-1000 nm, especially 30-500 nm, for example 40 nm, 50 nm, 80 nm, 100 nm, 120 nm, 150 nm, 200 nm, 220 nm, 250 nm, 300 nm, 400 nm, 700 nm, 1200 nm or 1500 nm.
[0044] Optionally, the oxide of the sulfide electrolyte is obtained by oxidizing the sulfide electrolyte. Specifically, in the corresponding processing of the electrolyte membrane, the electrolyte matrix is formed by coating or casting, and the electrolyte matrix is a membrane structure, a layer structure or a thin sheet structure. One side of the electrolyte matrix is oxidized, and at least part of the electrolyte matrix is oxidized to form a second electrolyte layer, that is, the second electrolyte layer is obtained by oxidation of part of the electrolyte matrix, and the unoxidized electrolyte matrix part constitutes the first electrolyte layer. Thus, by oxidizing the electrolyte matrix, an oxide layer structure can be generated by in-situ reaction on the electrolyte matrix, and the oxide layer structure constitutes the second electrolyte layer. The second electrolyte layer has a smaller thickness, which can avoid increasing the weight of the battery. The second electrolyte layer is obtained by oxidizing the electrolyte matrix, and does not need to be obtained by a separate forming process such as coating, which can reduce the production process and production cost of the electrolyte membrane.
[0045] Optionally, the second electrolyte layer includes an extension layer close to the positive electrode connection side, the thickness of the extension layer is 8-100nm, such as 15nm, 20nm, 25nm, 40nm, 50nm or 70nm, and the molar ratio of sulfur atoms to oxygen atoms in the extension layer is 1:(0.1-5), such as 1:0.15, 1:0.3, 1:0.5, 1:0.8, 1:1, 1:1.5, 1:2, 1:2.5 or 1:3. The extension layer can effectively block the first electrolyte layer and the positive electrode layer, and avoid chemical reaction between the first electrolyte layer and the positive electrode layer.
[0046] In a second aspect, the present disclosure provides an all-solid-state battery, comprising a positive electrode layer, a negative electrode layer, and an electrolyte membrane located between the positive electrode layer and the negative electrode layer, wherein the electrolyte membrane is the electrolyte membrane as described in the above technical solution, the electrolyte membrane is connected to the negative electrode layer through the first electrolyte layer, and the electrolyte membrane is connected to the positive electrode layer through the second electrolyte layer. The first electrolyte layer of the electrolyte membrane is connected to the positive electrode layer through the positive electrode connection side, and is connected to the negative electrode layer through the negative electrode connection side.
[0047] The positive electrode layer may be the positive electrode layer as described in the first aspect of the present disclosure, and the negative electrode layer may be the negative electrode layer as described in the first aspect of the present disclosure.
[0048] In a third aspect, the present disclosure provides a method for preparing an all-solid-state battery, wherein the all-solid-state battery may be the all-solid-state battery as described in the above technical solution, and the method comprises:
[0049] Step 11, oxidizing one side of the electrolyte matrix to obtain an electrolyte membrane.
[0050] Specifically, the electrolyte matrix includes at least one sulfide electrolyte, and the electrolyte matrix may have the same material as the existing electrolyte layer. Optionally, the sulfide electrolyte is at least one of LPSC, LPSBr, LSPS and LPSI.
[0051] The temperature of the oxidation treatment is 70-250°C, preferably 80-200°C, for example 100°C, 120°C, 150°C, 160°C, 180°C or 220°C.
[0052] The oxidation treatment time is 0.3-12 h, preferably 0.5-10 h, for example 0.5 h, 0.8 h, 1 h, 2 h, 3 h, 4 h, 5 h or 8 h.
[0053] The electrolyte membrane includes a first electrolyte layer and a second electrolyte layer formed by subjecting a portion of the electrolyte matrix to the oxidation treatment, wherein the unoxidized portion of the electrolyte matrix constitutes the first electrolyte layer.
[0054] Step 12, connecting the electrolyte membrane to the positive electrode layer and the negative electrode layer respectively to obtain an all-solid-state battery including the electrolyte membrane, the positive electrode layer and the negative electrode layer, wherein the first electrolyte layer is connected to the negative electrode layer, and the second electrolyte layer is connected to the positive electrode layer.
[0055] Specifically, the first electrolyte layer of the electrolyte membrane is connected to the negative electrode layer of the all-solid-state battery, and the second electrolyte layer of the electrolyte membrane is connected to the positive electrode layer of the all-solid-state battery to assemble the all-solid-state battery.
[0056] Optionally, before step 11, the method further includes step 10: obtaining an electrolyte matrix by coating and drying the electrolyte slurry.
[0057] The coating may be cast coating or other coating methods. The coating includes coating the electrolyte slurry on a substrate, the substrate may be a PET substrate or a metal substrate, the metal substrate may be an aluminum substrate, a copper substrate or a steel substrate, for example, the metal substrate is set to be an aluminum foil, a copper foil or a steel foil.
[0058] Optionally, in step 11, the substrate and the electrolyte matrix are placed together in an oxidizing atmosphere, such as an oxygen atmosphere or compressed air, and the electrolyte matrix is oxidized at a preset temperature, so that the side of the electrolyte matrix away from the substrate is exposed to the oxygen atmosphere or compressed air, and the side of the electrolyte matrix away from the substrate can be oxidized to form a second electrolyte layer on this side, and the unoxidized portion of the electrolyte matrix constitutes the first electrolyte layer.
[0059] Preferably, the compressed air has a preset moisture content. Optionally, the compressed air is compressed air with a dew point of -60°C to -20°C.
[0060] Correspondingly, in step 12, the electrolyte membrane is connected to the positive electrode layer and the negative electrode layer in sequence. Specifically, the electrolyte membrane on the substrate is first connected to the positive electrode layer, and the electrolyte membrane and the substrate are separated. For example, the electrolyte membrane on the substrate is transferred or pad printed to the positive electrode layer, so that the second electrolyte layer of the electrolyte membrane is connected to the positive electrode layer, and then the first electrolyte layer of the electrolyte membrane is connected to the negative electrode layer.
[0061] In a fourth aspect, the present disclosure provides a method for preparing an all-solid-state battery, wherein the all-solid-state battery may be the all-solid-state battery as described in the above technical solution, and the method comprises:
[0062] Step 21, connecting the electrolyte matrix to the negative electrode layer, or forming the electrolyte matrix on one side of the negative electrode layer to obtain a first composite.
[0063] Specifically, the electrolyte matrix includes at least one sulfide electrolyte, the electrolyte matrix may have the same material as the existing electrolyte layer, and the first composite includes the electrolyte matrix and the negative electrode layer. Optionally, the sulfide electrolyte is at least one of LPSC, LPSBr, LSPS and LPSI.
[0064] Optionally, before the electrolyte matrix is connected to the negative electrode layer, the method includes: coating and drying the electrolyte slurry to obtain the electrolyte matrix. The coating may be a cast coating or other coating methods. The coating includes coating the electrolyte slurry on a substrate, the substrate may be a PET substrate or a metal substrate, the metal substrate may be an aluminum substrate, a copper substrate or a steel substrate, for example, the metal substrate is set to an aluminum foil, a copper foil or a steel foil.
[0065] The connecting the electrolyte matrix to the negative electrode layer includes: connecting the electrolyte matrix on the substrate to the negative electrode layer and separating the electrolyte matrix from the substrate, for example, transferring or pad printing the electrolyte matrix on the substrate to the negative electrode layer so that the electrolyte matrix is connected to the negative electrode layer.
[0066] The electrolyte matrix is formed on one side of the negative electrode layer, including: coating the electrolyte slurry on one side of the negative electrode layer, and drying the coated electrolyte slurry to form the electrolyte matrix. The coating can be cast coating or other coating methods, thereby directly forming the electrolyte matrix on one side of the negative electrode layer.
[0067] Step 22, oxidizing the side of the electrolyte matrix away from the negative electrode layer to obtain a second composite including an electrolyte membrane, wherein the electrolyte membrane is obtained by oxidizing the electrolyte matrix, the oxidation treatment temperature is 70-250°C, and the oxidation treatment time is 0.3-12h.
[0068] Specifically, the electrolyte membrane includes a first electrolyte layer and a second electrolyte layer formed by a portion of the electrolyte matrix being subjected to the oxidation treatment, and the unoxidized electrolyte matrix portion constitutes the first electrolyte layer.
[0069] Optionally, the first composite is placed in an oxidizing atmosphere, such as an oxygen atmosphere or compressed air, and the electrolyte matrix is oxidized at a preset temperature, whereby the side of the electrolyte matrix away from the negative electrode layer is exposed to the oxygen atmosphere or compressed air, and the side of the electrolyte matrix away from the negative electrode layer can be oxidized to form a second electrolyte layer on this side, and the unoxidized portion of the electrolyte matrix constitutes the first electrolyte layer.
[0070] The temperature of the oxidation treatment is 70-250°C, preferably 80-200°C, for example 100°C, 120°C, 150°C, 160°C, 180°C or 220°C.
[0071] The oxidation treatment time is 0.3-12 h, preferably 0.5-10 h, for example 0.5 h, 0.8 h, 1 h, 2 h, 3 h, 4 h, 5 h or 8 h.
[0072] Preferably, the compressed air has a preset moisture content. Optionally, the compressed air is compressed air with a dew point of -60°C to -20°C.
[0073] Step 23, connecting the second composite with the positive electrode layer through the electrolyte membrane to obtain an all-solid-state battery including the electrolyte membrane, the positive electrode layer and the negative electrode layer.
[0074] Specifically, the second electrolyte layer of the electrolyte membrane is connected to the positive electrode layer to assemble the all-solid-state battery.
[0075] The electrolyte membrane, all-solid-state battery and preparation method thereof provided by the present disclosure are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present disclosure.
[0076] Comparative Example 1
[0077] In the positive electrode layer of the halide all-solid-state battery: Ni92 small particle single crystals are used, with a particle size of 3-6μm, accounting for 85% by mass; the halide electrolyte uses LiNbOCl4, with a particle size of 0.5-2μm, a room temperature ion conductivity of 5.5-6.0mS / cm, and a mass proportion of about 14%; the binder uses PTFE, accounting for about 0.5% by mass; the conductive carbon uses VGCF, accounting for about 0.5% by mass. The thickness of the positive electrode layer is 100μm.
[0078] In the negative electrode layer: micron Si is used, with a particle size of 0.8-1.5 μm, accounting for about 98% by mass; CMC is used as a binder, accounting for about 2% by mass. The thickness of the negative electrode layer is 20 μm.
[0079] The electrolyte layer uses a double-layer cast coating film. On the PET substrate, a Li3InCl6 halide electrolyte layer with a final thickness of about 5μm is coated, and after drying, a LPSC (Li6PS5Cl) sulfide electrolyte layer with a final thickness of 25μm is coated to construct a double-layer electrolyte layer. After drying, it is transferred to the surface of the silicon negative electrode layer, and the sulfide electrolyte layer is located between the halide electrolyte layer and the silicon negative electrode layer.
[0080] Finally, the dry cathode film and the Al current collector are compounded on the surface of the Li3InCl6 halide electrolyte layer and stacked. The battery is a double-sided design, including the Al current collector, the cathode layer, the halide electrolyte layer, the sulfide electrolyte layer, the cathode layer, the cathode current collector (copper current collector), the cathode layer, the sulfide electrolyte layer, the halide electrolyte layer, the cathode layer, and the Al current collector. The cathode surface loading capacity of the battery is designed to be 5 mAh / cm 2 , positive electrode area 10×10cm 2 , single-sided design capacity 500mAh, double-sided design, total 1Ah.
[0081] Comparative Example 2
[0082] The preparation method of the positive electrode layer and the negative electrode layer of the halide all-solid-state battery is the same as that of Comparative Example 1.
[0083] The electrolyte layer adopts a single-layer cast coating film, which is different from comparative example 1 in that the Li3InCl6 halide electrolyte layer is eliminated. On the PET substrate, a LPSC (Li6PS5Cl) sulfide electrolyte layer with a final thickness of 25 μm is coated, and after drying, it is transferred to the surface of the silicon negative electrode layer.
[0084] Finally, the dry cathode film and the Al current collector are composited to the surface of the Li3InCl6 halide electrolyte layer and laminated. The battery is a double-sided design, including the Al current collector, the positive electrode layer, the sulfide electrolyte layer, the negative electrode layer, the negative electrode current collector (copper current collector), the negative electrode layer, the sulfide electrolyte layer, the positive electrode layer, and the Al current collector. The positive electrode surface loading of the battery is designed to be 5mAh / cm 2 , positive electrode area 10×10cm 2 , single-sided design capacity 500mAh, double-sided design, total 1Ah.
[0085] Example 1
[0086] The preparation method of the positive electrode and the negative electrode of the halide all-solid-state battery is the same as that in Comparative Example 1.
[0087] On the PET substrate, a layer of LPSC (Li6PS5Cl) sulfide electrolyte matrix with a final thickness of 25μm is coated. After heat treatment at 120℃ for 3h in a pure O2 atmosphere, an electrolyte membrane including a first electrolyte layer and a second electrolyte layer is obtained. The electrolyte membrane is transferred to the surface of the positive electrode layer and finally compounded to the surface of the silicon negative electrode and stacked. Figure 1 The cross-sectional morphology of the electrolyte membrane and the distribution of O, Cl and S elements are shown. The thickness of the second electrolyte layer is about 200 nm, and the oxide layer of the sulfide electrolyte matrix constitutes the second electrolyte layer.
[0088] The battery is a double-sided design, including an Al current collector, a positive electrode layer, a second electrolyte layer, a first electrolyte layer, a negative electrode layer, a negative electrode current collector (copper current collector), a negative electrode layer, a first electrolyte layer, a second electrolyte layer, a positive electrode layer, and an Al current collector. The positive electrode surface loading of the battery is designed to be 5 mAh / cm 2 , positive electrode area 10×10cm 2 , single-sided design capacity 500mAh, total 1Ah.
[0089] Example 2
[0090] The positive and negative electrode preparation methods and battery structure of the halide all-solid-state battery are the same as those in Example 1.
[0091] On the PET substrate, a layer of LPSC (Li6PS5Cl) sulfide electrolyte matrix with a final thickness of 25μm is coated, and after being heat treated at 120℃ for 3h in a -60℃ dew point compressed air atmosphere, it is transferred to the surface of the positive electrode layer and finally composited to the surface of the silicon negative electrode and stacked. The positive electrode surface loading of the battery is designed to be 5mAh / cm 2 , positive electrode area 10×10cm 2 , single-sided design capacity is 500mAh, totaling 1Ah.
[0092] Example 3
[0093] The positive and negative electrode preparation methods and battery structure of the halide all-solid-state battery are the same as those in Example 1.
[0094] On the PET substrate, a layer of LPSC (Li6PS5Cl) sulfide electrolyte matrix with a final thickness of 25μm is coated and transferred to the negative electrode surface. The electrolyte matrix and the negative electrode are heat treated at 120℃ for 3h in a pure O2 atmosphere and then composited with the positive electrode layer and laminated. The positive electrode surface loading of the battery is designed to be 5mAh / cm 2 , positive electrode area 10×10cm 2 , single-sided design capacity 500mAh, total 1Ah.
[0095] Example 4
[0096] The positive and negative electrode preparation methods and battery structure of the halide all-solid-state battery are the same as those in Example 1.
[0097] On the PET substrate, a layer of LPSC (Li6PS5Cl) sulfide electrolyte matrix with a final thickness of 25μm is coated and transferred to the negative electrode surface. The electrolyte matrix and the negative electrode are heat treated at 120℃ for 3h in a -60℃ dew point compressed air atmosphere, and then composited with the positive electrode layer and laminated. The positive electrode surface loading of the battery is designed to be 5mAh / cm 2 , positive electrode area 10×10cm 2 , single-sided design capacity 500mAh, total 1Ah.
[0098] After the LPSC electrolyte matrix in the above-mentioned Example 1 and Example 2 is oxidized by oxygen or dry compressed air, the depth at which the oxygen atomic content is lower than 2% element abundance is detected by Tof-SIMS etching and recorded as the thickness of the LPSC oxide layer. After testing, the thickness of the oxide layer in Example 1 is about 192nm, and the thickness of the oxide layer in Example 2 is about 207nm. Dry compressed air contains a very small amount of water, which assists in corroding the surface of the LPSC film, thereby making the oxide layer thicker.
[0099] After the LPSC electrolyte matrix in the above-mentioned Example 1 was oxidized by oxygen, it was sheared to obtain a cross section, and its morphology was observed by field emission scanning electron microscopy (SEM), and the distribution of oxygen elements was scanned by EDX, as shown in the attached figure. Figure 1 The boundary between the oxide layer and the LPSC electrolyte is fuzzy, and the distribution of oxygen elements shows that the layer thickness is about 200nm.
[0100] The data statistics of the comparative examples and embodiments at room temperature 30°C and 0.05C for the first charge and discharge capacity, and after 50 cycles at 0.1C are shown in Table 1.
[0101] Table 1
[0102]
[0103] As shown in Table 1, the battery in Comparative Example 1 in which the LIC layer is added to separate the LPSC sulfide electrolyte layer and the halide composite positive electrode is charged and discharged normally, while the LPSC sulfide electrolyte layer in Comparative Example 2 is in direct contact with the halide composite positive electrode to cause serious side reactions, resulting in huge internal resistance and almost no cycling ability; the electrolyte membrane that is oxidized by O2 or compressed air to construct an oxidized interface thin layer (second electrolyte layer) can effectively reduce the internal resistance and achieve a higher discharge capacity.
[0104] If the thickness of the oxide layer is controlled within 50nm, the internal resistance contributed by the electrolyte layer increases by about 48.3mΩ·cm, based on the conductivity decreasing from 3mS / cm to 0.1mS / cm. 2 ; The internal resistance of commercial ternary liquid lithium-ion batteries is generally 1000-10000mΩ·cm 2 The oxide layer contributes very little to the increase in the impedance of the battery cell as a whole and can be ignored. The existing halide pad layer has a thickness of 5 μm and a conductivity of 0.3 mS / cm. The internal resistance increased by this layer is about 1666 mΩ·cm2, which is far beyond the low internal resistance that can be achieved by the solution provided in the present disclosure.
[0105] The above description has fully disclosed the specific embodiments of the present disclosure. It should be pointed out that any changes made by technicians familiar with the field to the specific embodiments of the present disclosure do not deviate from the scope of the claims of the present disclosure. Accordingly, the scope of the claims of the present disclosure is not limited to the aforementioned specific embodiments.
Claims
1. An electrolyte membrane for an all-solid-state battery, characterized in that: It includes a first electrolyte layer, which includes at least one sulfide electrolyte. The first electrolyte layer includes a positive electrode connection side and a negative electrode connection side that are arranged opposite to each other. The positive electrode connection side is used to connect to the positive electrode of the solid-state battery, and the negative electrode connection side is used to connect to the negative electrode of the solid-state battery. The positive electrode connection side of the first electrolyte layer is provided with a second electrolyte layer, and the second electrolyte layer includes an oxide of the sulfide electrolyte.
2. The electrolyte membrane according to claim 1, characterized in that The thickness of the second electrolyte layer is 10-2000 nm.
3. The electrolyte membrane according to claim 2, characterized in that The oxide of the sulfide electrolyte is obtained by oxidizing the sulfide electrolyte.
4. The electrolyte membrane according to any one of claims 1 to 3, characterized in that: The sulfide electrolyte is at least one of LPSC, LPSBr, LSPS and LPSI.
5. The electrolyte membrane according to any one of claims 1 to 3, characterized in that: The thickness of the first electrolyte layer is 15-100 μm; the thickness of the second electrolyte layer is 20-1000 nm.
6. The electrolyte membrane according to any one of claims 1 to 3, characterized in that: The second electrolyte layer includes an extension layer close to the positive electrode connection side, the thickness of the extension layer is 8-100 nm, and in the extension layer, the molar ratio of sulfur atoms to oxygen atoms is 1:(0.1-5).
7. An all-solid-state battery, comprising a positive electrode layer, a negative electrode layer and an electrolyte membrane located between the positive electrode layer and the negative electrode layer, characterized in that: The electrolyte membrane is the electrolyte membrane according to any one of claims 1 to 6, the electrolyte membrane is connected to the negative electrode layer through the first electrolyte layer, and the electrolyte membrane is connected to the positive electrode layer through the second electrolyte layer.
8. A method for preparing an all-solid-state battery, characterized in that: include: Performing oxidation treatment on one side of an electrolyte matrix to obtain an electrolyte membrane, wherein the electrolyte matrix includes at least one sulfide electrolyte, the oxidation treatment temperature is 70-250° C., the oxidation treatment time is 0.3-12 hours, and the electrolyte membrane includes a first electrolyte layer and a second electrolyte layer formed by a portion of the electrolyte matrix after the oxidation treatment; The electrolyte membrane is connected to the positive electrode layer and the negative electrode layer respectively to obtain an all-solid-state battery including the electrolyte membrane, the positive electrode layer and the negative electrode layer, wherein the first electrolyte layer is connected to the negative electrode layer, and the second electrolyte layer is connected to the positive electrode layer.
9. The preparation method according to claim 8, characterized in that: The oxidation treatment comprises: placing one side of the electrolyte matrix in a compressed air atmosphere or an oxygen atmosphere, and treating at 80-200° C. for 0.5-10 hours.
10. A method for preparing an all-solid-state battery, characterized in that: include: Connecting an electrolyte matrix to the negative electrode layer or forming the electrolyte matrix on one side of the negative electrode layer to obtain a first composite, wherein the electrolyte matrix includes at least one sulfide electrolyte; The electrolyte matrix is subjected to oxidation treatment on a side away from the negative electrode layer to obtain a second composite body including an electrolyte membrane, wherein the electrolyte membrane is obtained by oxidation treatment of the electrolyte matrix, the oxidation treatment temperature is 70-250° C., and the oxidation treatment time is 0.3-12 h; The second composite is connected to the positive electrode layer through the electrolyte membrane to obtain an all-solid-state battery including the electrolyte membrane, the positive electrode layer and the negative electrode layer.
11. The preparation method according to claim 10, characterized in that: The oxidation treatment comprises: placing the first composite body in a compressed air atmosphere or an oxygen atmosphere at 80-200° C. for 0.5-10 hours.
Citation Information
Cited By
Three-layer heterogeneous integrated solid electrolyte membrane, preparation method thereof and all-solid-state lithium battery
CN121331919A